The Importance of New EBMT Criteria on the Diagnosis of Veno-Occlusive Liver Disease in Children - Füssiová, Mária; Švec, Peter; Horáková, Júlia; Sedláček, Petr; Rohoň, Peter; Celec, Peter; Boďová, Ivana; Adamčáková, Jaroslava; Sýkora, Tomáš; Dobšinská, Veronika; Pozdechová, Miroslava; Dóczyová, Dominika; et al. (Journal of clinical medicine, 2023)
BACKGROUND: Early recognition and specific therapy facilitate a favorable disease course in hepatic venous-occlusive disease (HVOD) following hematopoietic stem cell transplantation (HCT). Diagnostic and classification criteria, published by the European Society for Blood and Marrow Transplantation (EBMT), better account for clinical differences in disease presentation in pediatric populations. OBJECTIVES: To compare the course of HVOD in children before and after the implementation of new EBMT criteria. MATERIAL AND METHODS: The study retrospectively evaluates 26 HVODs in 179 children treated in a single HCT unit (Slovakia) comparing the period of 2014-2017 using the Baltimore and modified Seattle criteria with the period of 2018-2021, when new EBMT criteria were adopted. RESULTS: No difference in HVOD incidence (11.2% vs. 14.8%, p = 0.46) and in time of diagnosis post-HCT (15.6 days vs. 15.7 days, p = 0.75) was found. With EBMT criteria we observed more frequent anicteric disease at diagnosis (50% vs. 87.5%, p = 0.04), lower serum bilirubin at diagnosis (3.4 mg/dL vs. 1.23 mg/dL, p = 0.045), and non-significant trends of shorter defibrotide treatment (21.7 days vs. 15.6 days, p = 0.73), decreased mortality (30% vs. 6.2%, p = 0.10) and shorter hospitalization (73.1 days vs. 59.6 days, p = 0.54). CONCLUSIONS: Different time periods around the implementation of new criteria are evaluated, underling that pediatric EBMT criteria for post-transplant HVOD diagnosis appear more sensitive.